Impact Of Service Quality On Customer Behavioral Intention In Malaysia Telecommunication Industry - Tahir, Khafiz (2004)
The objectives of this study are to provide overview of service quality and discuss its relationship with customer behavioral intentions in Malaysian telecommunication industry; assess the service quality level of Malaysian telecommunication companies in term of its selected dimensions. The resullt indicate that service quality do not have direct impact to the customer behavioral intentions and market leadership.